HCI preliminary study and implementation for a LoRa based SAR system - Christos Bouras; Apostolos Gkamas; Spyridon Katsampiris (The 12th International Conference on Sensor Device Technologies and Applications (SENSORDEVICES 2021), November 14 – 18, 2021, Athens, Greece, 2021)
The subject of this paper is the study and implementation of a Long Range (LoRa) based Search and Rescue system that can help in the localization of people having a high risk of going missing. These people may suffer from dementia, attention disturbance, and distraction, or disease in the autism spectrum, and it is of great importance to be found in a specific time frame, as their life can be in danger. The system is based on LoRa network architecture that enables both long-range communication and low energy consumption. In this paper aspects of the human-computer interaction were taken into consideration in contrast to the majority of the related papers, and is the proposed system is evaluated using heuristic evaluation and questionnaires.